A Study of Resin as Master Jewellery Material, Surface Quality and Machining Time Improvement by Implementing Appropriate Cutting Strategy - Puspaputra Paryana (MATEC Web of Conferences, 2017)
This paper deals with a research about art and jewellery product machining that focused in the selection of appropriate material for jewellery master which is machined by CNC. CNC is used for better surface finish for no undercut design and more complex ornament. The need of production speed requires minimum process without reducing the quality of detail ornament significantly. Problems occur when high surface quality is required. In that condition high speed spindle is used with low feeding speed, as a result is high temperature in cutter-material area will melt the resin and build the build-up edge (BUE). Due to the existence of BUE, the cutting tool will no longer cut the resin, as a result the resin will then melt due to friction and the melt resin will then stuck on the relief and surface finish become worst and rework should be done. When required surface is achieved problem also occur in next going process, that is silicon mould making. Due to galvanization process for silicon at about 170°C, resin material may be broken or cracked. Research is then conducted to select appropriate resin type suitable for all production steps.